ANALYTICAL SUPPORT OF RISK ASSETS MANAGEMENT AS A COMPONENT OF FORMING A POSITIVE IMAGE OF THE ENTERPRISE - Панасюк, Валентина; Босий, Володимир; Шухманн, Вадим (SWorldJournal, 2024)
In the conditions of economic globalization, enterprises engaged in international financial activities face significant difficulties in the form of financial risks. Such a threat may result in loss of capital or failure to obtain profits as a result of ac